Strategi Penerapan Bauran Pemasaran Pada Kegiatan “Semarang Heritage Family Run 2022” - Feisyah Alifah Andini; Anisatul Auliya (Journal of Tourism and Economic, 2023)
In the research, the researcher aims to explore the 7P marketing mix strategy carried out at the "Semarang Heritage Family Run 2022" activity. This research used qualitative methods and research techniques through observation, interviews, and literacy studies. The results of this research lead to the results of the 7P marketing mix analysis carried out by the organizers of this activity so that careful planning is created, and the activity is successful and in demand. The research results showed that the application of the marketing mix used was effective in planning the maturity of event activities. The application of the marketing mix starts from determining the product that will be used as the core material of the planned activity, determining the price, the location of the activity, the promotion carried out, the human resources involved, physical evidence as material for consideration by potential activity participants, and the process as a series of implementation flows, assessed is quite good and has a positive effect on the satisfaction of activity participants.